2022
DOI: 10.1200/jco.2022.40.16_suppl.4051
|View full text |Cite
|
Sign up to set email alerts
|

Ramucirumab, avelumab, and paclitaxel (RAP) as second-line treatment in gastro-esophageal adenocarcinoma, a phase II trial of the Arbeitsgemeinschaft Internistische Onkologie (AIO).

Abstract: 4051 Background: Combination of ramucirumab and paclitaxel is a standard second line therapy in gastro-esophageal adenocarcinoma (GEAC) (RAINBOW trial, Wilke et al., 2014). We integrated the PD-L1 inhibitor avelumab into this regimen aiming for synergistic efficacy. Methods: In a multicenter phase II trial (NCT03966118) pts with metastatic GEAC, after progression on platinum / fluoropyrimidine based palliative 1st-line, ECOG 0 or 1, were treated with ramucirumab 8 mg/kg (d1,15) + avelumab 10 mg/kg (d1,15) + p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Furthermore, a phase II trial conducted by the Arbeitsgemeinschaft Internistische Onkologie (AIO) evaluated the effectiveness of combining avelumab, ramucirumab, and paclitaxel as second-line therapy for GEJC patients. The trial findings indicated a median OS of 9.4 months for CPS < 5 patients compared to 14.0 months for CPS ≥ 5 patients, underscoring the prognostic value of CPS in predicting the response to immunotherapy in GC patients [24]. In the MAHOGANY study, an exploration was conducted involving the amalgamation of the anti-HER2 monoclonal antibody (margetuximab) and the anti-PD-1 monoclonal antibody (pembrolizumab) in individuals afflicted by trastuzumab-resistant HER2-positive gastro-esophageal adenocarcinoma.…”
Section: Pd-l1 Expression As the Biomarker For Gc Immunotherapymentioning
confidence: 89%
“…Furthermore, a phase II trial conducted by the Arbeitsgemeinschaft Internistische Onkologie (AIO) evaluated the effectiveness of combining avelumab, ramucirumab, and paclitaxel as second-line therapy for GEJC patients. The trial findings indicated a median OS of 9.4 months for CPS < 5 patients compared to 14.0 months for CPS ≥ 5 patients, underscoring the prognostic value of CPS in predicting the response to immunotherapy in GC patients [24]. In the MAHOGANY study, an exploration was conducted involving the amalgamation of the anti-HER2 monoclonal antibody (margetuximab) and the anti-PD-1 monoclonal antibody (pembrolizumab) in individuals afflicted by trastuzumab-resistant HER2-positive gastro-esophageal adenocarcinoma.…”
Section: Pd-l1 Expression As the Biomarker For Gc Immunotherapymentioning
confidence: 89%
“…Furthermore, data from the ATTRACTION-2 trial of a Japanese intention to treat population indicated better clinical effects of nivolumab with prior ramucirumab use [ 112 ]. Most recently, avelumab with paclitaxel plus ramucirumab in the phase II RAP trial showed better outcomes compared with a Western population in the RAINBOW trial (median OS, 10.6 vs. 8.6 months) [ 113 ]. Other combinations of immune checkpoint inhibitors with VEGF-targeted therapy have been reported.…”
Section: Potential Regimens and Future Directionsmentioning
confidence: 99%